Computational simulation of progressive collapse of reinforced concrete rigid frame with reinforcement contact model. Issue 6 (June 2016) - Kim, Han-Soo; Ahn, Jae-Gyun; Ahn, Hyo-Seong
The advantage of using Autodyn, a specialized hydro-code for the analysis of explosion and impact, is its appropriateness for predicting the progressive collapse of a building when a column still has some load-bearing capacity left after a blast. However, the requirement of sharing nodes between volume elements for concrete and line elements for reinforcements hampers its application to the blast analysis of large-scale reinforced concrete structures. In this article, the blast analysis of a reinforced concrete frame structure is simulated using the reinforcement contact model in Autodyn. This modeling method shows structural behavior under blast load similar to that of a more precise model with reinforcement and concrete. Furthermore, this method allows for faster simulation of progressive collapse analysis for tall buildings. The effect of steel reinforcement patterns and spacing of stirrups in reinforced concrete beams is demonstrated by performing several progressive collapse analyses with the reinforcement contact model. Thus, the proposed modeling method can be effectively applied to the blast-loading progressive collapse analysis of a reinforced concrete frame structure.